A behavioural perspective on the effects of using performance measurement systems in the companies: Evidence from a case study - Lampreia, João; Major, Maria João (Dos Algarves, 2017)
The effects of Performance Measurement Systems (PMS) on people’s behaviour are relevant for an organization performance and success. Yet motivational and behavioural consequences of PMS are far from being understood. This study aims to go further regarding the consequences on people’s behaviour of using PMS in organizations. In order to collect data researchers conducted a case study in a Portuguese multi-national company. Evidence shows that the way in which managers understand a PMS influences in a significant way how they behave. The data also lends support to the claim that PMS influence motivation, perceptions, participation and job-related stress of managers.